IMPLICATIONS OF DUAL POSITIONS OF SHARIA SUPERVISORY BOARD ON THE EFFECTIVENESS OF SUPERVISION IN ISLAMIC FINANCIAL INSTITUTIONS - Habibah Arifin, Desi Siti; Kania, Dede; Anwar, Syahrul (Journal Of Sharia Banking, 2024)
The dual position of Sharia Supervisory Board (DPS) in Islamic financial institutions is a phenomenon that often occurs, both at the national and international levels. This practice has various implications for the effectiveness of supervision, which in turn has an impact on sharia compliance and the integrity of Islamic financial institutions. This study aims to analyse the impact of multiple DPS positions on the effectiveness of supervision, both in terms of regulations, ethics, and practices in the field. This research uses a descriptive qualitative approach to analyse the implications of dual positions of the Sharia Supervisory Board (DPS) on the effectiveness of supervision in Islamic financial institutions. The results show that concurrent positions can reduce the effectiveness of supervision due to potential conflicts of interest, time constraints, and excessive workload. On the other hand, concurrent positions also provide benefits in the form of a broader transfer of knowledge and experience for DPS. However, in order for supervision to remain optimal, firmer regulations are needed regarding the limitations of concurrent positions as well as strengthening internal and external supervisory mechanisms. The implications of this study provide recommendations to regulators and Islamic financial institutions to balance the aspects of efficiency and independence in the role of the Sharia Supervisory Board in order to maintain the sustainability of the Islamic financial industry.